Design Principles of the Rotary Type 9 Secretion System - Trivedi, Abhishek; Gosai, Jitendrapuri; Nakane, Daisuke; Shrivastava, Abhishek (Frontiers in Microbiology, 2022)
The Fo ATP synthase, the bacterial flagellar motor, and the bacterial type 9 secretion system (T9SS) are the three known proton motive force driven biological rotary motors. In this review, we summarize the current information on the nuts and bolts of T9SS. Torque generation by T9SS, its role in gliding motility of bacteria, and the mechanism via which a T9SS-driven swarm shapes the microbiota are discussed. The knowledge gaps in our current understanding of the T9SS machinery are outlined.